Child/Adolescent’s ADHD and Parenting Stress: The Mediating Role of Family Impact and Conduct Problems - Muñoz-Silva, Alicia; Lago-Urbano, Rocio; Sanchez-Garcia, Manuel; Carmona-Márquez, José (Frontiers in Psychology, 2017)
Objective: The demands of parenting are usually associated with some stress, and elevated levels of stress may affect the parent-child relationships and parenting practices. This is especially the case of families where children have special needs conditions or disorders, like Attention Deficit Hyperactivity Disorder (ADHD). Method: This study examined parenting stress among mothers of children and adolescents with ADHD. The sample comprised 126 mothers of girls (36; 29%) and boys (90; 71%) aged 6 to 17 years old. Results: Mothers reported their own stress levels as well as the children and adolescents’ variables (severity of their ADHD symptoms, conduct and emotional problems) and family-contextual variables (negative impact on family’s social life, impact on couple relationship, and perceived social support). Hierarchical multiple regression showed that (a) negative impact on social life and conduct problems were the strongest predictors of mother’s stress. Bootstrap mediation analyses revealed that (b) the association between child and adolescent’s ADHD and parenting stress was mediated by children’s conduct problems and by negative impact on family’s social life, and not by children’ emotional problems nor by mother’s perceived social support. The mediation analysis also suggested (c) a pathway from child/adolescent’s ADHD through children’s conduct problems and then through their negative impact on family’s social life to mother’s parenting stress. Conclusions: These results suggest that both child/adolescent’s and family factors should be considered in the designing of interventions for reducing parenting stress in families of children and adolescents with ADHD.